The effect of aerobic soil conditions, soil volume and sowing date on the development of four tropical rice varieties grown in the greenhouse - Clerget, Benoit; Bueno, Crisanta (Commonwealth Scientific and Industrial Research Organisation, 2013)
Rice has generally been reported to yield less in aerobic soil conditions than in flooded soil conditions, in association with delayed anthesis and a reduction in height. A greenhouse experiment was conducted and repeated twice with four rice varieties grown in either flooded or nearly-saturated aerobic soil, in either large or small pots. The rate of leaf appearance was recorded weekly until heading time, when plants were harvested for shoot and root biomass. The kinetics of leaf appearance was generally trilinear with longer phyllochrons in the May sowing. Pot size had only a small effect whereas aerobic soil conditions slowed down the rate of leaf initiation, which consequently delayed panicle initiation and heading date and thus increased the duration of the tillering phase and finally the number of tillers. Surprisingly, the four varieties showed a significant response to sowing date, especially IR72, which headed 21 days later and after the expansion of two more leaves in the May sowing. The aerobic soil conditions and sowing date have thus changed the rate of development of rice plants and this trait has appeared to be the initial link of a chain of consequences in a series of traits known to be affected by these factors.